NAD+ Homeostasis in Diabetic Kidney Disease - Xu, Jing; Kitada, Munehiro; Koya, Daisuke (Frontiers in Medicine, 2021)
The redox reaction and energy metabolism status in mitochondria is involved in the pathogenesis of metabolic related disorder in kidney including diabetic kidney disease (DKD). Nicotinamide adenine dinucleotide (NAD+) is a cofactor for redox reactions and energy metabolism in mitochondria. NAD+ can be synthesized from four precursors through three pathways. The accumulation of NAD+ may ameliorate oxidative stress, inflammation and improve mitochondrial biosynthesis via supplementation of precursors and intermediates of NAD+ and activation of sirtuins activity. Conversely, the depletion of NAD+ via NAD+ consuming enzymes including Poly (ADP-ribose) polymerases (PARPs), cADPR synthases may contribute to oxidative stress, inflammation, impaired mitochondrial biosynthesis, which leads to the pathogenesis of DKD. Therefore, homeostasis of NAD+ may be a potential target for the prevention and treatment of kidney diseases including DKD. In this review, we focus on the regulation of the metabolic balance of NAD+ on the pathogenesis of kidney diseases, especially DKD, highlight benefits of the potential interventions targeting NAD+-boosting in the treatment of these diseases.